Length based-spawning potential ratio (LB-SPR) model for estimating successful adaptation of invasive crayfish (Cherax quadricarinatus, Morten) in Java. Issue 1 (February 2021) - Santoso, A; Yonvitner,; Akmal, S G
Abstract: Successful adaptation of invasive crayfish influence by environmental factors and biological factors, especially reproduction. Therefore needed important to collect and evaluate crayfish biology data, particularly the length, reproduction, and selectivity parameter. This parameter is also helpful in data-poor management in fisheries because it can be connected to management's tactical strategy. The invasive crayfish data collect in 5 five locations in Java island, i.e., Cirebon, Semarang, Surabaya, Yogyakarta, and Cilacap. SPR analysis using application link to http://barefootecologist.com.au/lbspr after maturity, size capture, and length-frequency analysis. The result of these research shows average length in Cirebon (71 ±18, 38), in Semarang (53 ±0, 00), in Surabaya (83 ±3, 54), in Yogya (87, 5 ±15, 91), and Cilacap (65 ±6, 36) mm. Spawning potential ratio in Cirebon 68%, in Semarang 37%, in Surabaya 100%, in Yogyakarta 81%, and Cilacap 0, 62%, with the total average in five-station is 62%. The first maturity at 50% population, Selectivity length (50%) in Cirebon 38, 72 mm, Semarang 49, 68 mm, Surabaya 37, 96 mm, Yogya 37, 68 mm and Cilacap 42, 29 mm. SPR result that more than 40% shown that successfully spawning in Java relatively high and spread, and adaptation is also going well. The distribution in wild habitat potential influences native species, and it even causes extinction. Therefore it is necessary to prepare management steps to protect native species from invasive crayfish.